The Right to Religious Freedom, with Particular Reference to Same-Sex Marriage* - Perry, Michael J. (Journal of law, religion and state, 2012)
In this essay, I elaborate and defend the internationally recognized human right to religious freedom. I then pursue the implications of the right for government’s exclusion of same-sex couples from of civil marriage.